A minimal biophysical model for the temperature dependence of CO2 fixation rates based on macromolecular rate theory - Erica J. Prentice; Margaret M. Barbour; Vickery L. Arcus (PLoS ONE, 2025)
Accurately predicting how the global environment will change under continued CO2 and temperature increases is currently a critical issue. Predictions are dependent on global models that represent this complex system of natural and anthropogenic inputs, responses, and feedback loops. These models must include accurate descriptions of complex biological processes such as photosynthesis, which is currently responsible for the removal of 123 petagrams of atmospheric carbon annually. Here, we develop a simplified approach to model the effect of concurrent changes in temperature and CO2 concentrations on the rate of C3 carbon fixation. The model simplifies the temperature response of the CO2 fixation pathway into a three-parameter curve (as modelled by macromolecular rate theory, MMRT), which incorporates the limitations of RuBisCO kinetics, and CO2 and O2 solubility as simple system constraints. This framework fully accounts for the temperature and CO2 dependence of CO2 fixation rates in sweet potato (Ipomoea batatas) leaves with just three parameters, in combination with defined biophysical constraints.